The Development Status and Improvement Strategies of Chinese Rural Wellness Tourism Based on Social Psychology (Journal of Global Humanities and Social Sciences, 2025)
China has a vast territory, and the vast rural areas have very rich tourism resources. Rural health tourism not only effectively promotes the development of rural economy, but also aims at the problems existing in the development of rural health vacation tourism. However, only on the basis of rational development of natural tourism resources can we better meet the needs of consumers.Social psychology can guide social groups to make rational use of natural resources and green consumption through various forms, and reasonably develop rural recuperation and vacation tourism. From the perspective of social psychology, this paper discusses whether people can effectively and reasonably use natural resources, green consumption and reasonable development of resources.Take market development as the important guidance and government policy support as the important support, give play to the core role of health culture resources, promote the in-depth integration of rural tourism resources, and escort the healthy and sustainable development of rural medical care and holiday tourism.